Extracellular Vesicles Derived from Lung Cancer Cells Induce Transformation of Normal Fibroblasts into Lung Cancer-Associated Fibroblasts and Promote Metastasis of Lung Cancer by Delivering lncRNA HOTAIR - Xiaoxuan Zhang; Yan Zhang; Xin Qiu; Jing Cai; Zhenzhou Yang; Fangzhou Song (Hindawi Limited, 2022)
Human lung cancer (LC) cells A549/H358, normal lung epithelial cells BEAS-2B, and lung normal fibroblasts (NFs) were cultured, followed by transfection of H358 cells with HOTAIR shRNA. Extracellular vesicles (EVs) extracted from H358 cells were identified. The internalization of Dil-labeled-EVs by NFs was tested, and protein levels of cancer-associated fibroblast (CAF) surface markers, inflammatory cytokines, cell proliferation, invasion, and migration, and lncRNA HOTAIR levels were determined. A549 cells were cultured in an H358-EVs-treated conditioned medium of NFs (NFCM), followed by intravenous injection of A549 cells into nude mice. The lesions and Ki-67-positive cells in lung tissues were measured. The results showed that tumor cell-derived EVs (T-EVs) motivated the transformation of NFs into CAFs. Specifically, EVs can be internalized by NFs, and the protein levels of CAF surface markers and inflammation levels were elevated in H358-EVs-treated NFs. The proliferation, invasion, and migration of A549 cells cultured in T-EVs-treated NFCM were increased. H358-EVs carried HOTAIR into NFs and promoted the transformation of NFs into CAFs. Inhibition of HOTAIR partially reversed the promoting effect of H358-EVs on the transformation of NFs into CAFs and invasion and migration of LC cells. T-EVs promoted metastasis of LC in vivo by transforming NFs into CAFs.